PRARE ツイセキ アンテナ ノ ショウワ キチ セッチ ト ウンヨウ - 渋谷, 和雄; シブヤ, カズオ; 金尾, 政紀; カナオ, マサキ; 東, 敏博; アズマ, トシヒロ; 青木, 茂; アオキ, シゲル; Shibuya, Kazuo; Kanao, Masaki; Higashi, Toshihiro; Aoki, Shigeru (2000)
P(論文) PRAREとはPrecise Range and Range-rate Equipmentの略称である。その地上局アンテナが1997年3月, 第38次日本南極地域観測隊(第38次隊)によって昭和基地に設置された。アンテナ支柱と国際GPS観測局網(IGS網)の昭和基地アンテナ基準点との間はGPS受信機による相対測位によって結ばれ, 1994年国際測地基準座標系(ITRF94)における座標値は元期1997.0においてX_P=1766500.399m, Y_P=1460251.211m, Z_P=-5932214.446mと求められた。15秒間隔で得られるERS-2衛星までの測距データは1997年3月から9月末まではほぼ100%(1週あたり約2500分)得られたが, その後受信数は急激に減少した。これは, レドーム内が低温になり, Xバンドの受信ケーブルが劣化したためと思われる。測距データに対してリアルタイムの対流圏補正は出来なかったが, 地上気象観測データを用いた後処理によると, 標準誤差が補正なしの50cmに対して, 補正ありだと30cmまで改善されることがわかった。PRARE精密軌道解を用いた, レーダー高度計や合成開口レーダーデータの応用研究については別途報告する。 A PRARE (Precise Range and Range-rate Equipment) tracking antenna was installed by the 38th Japanese Antarctic Research Expedition (JARE-38) at Syowa Station (69.0°S, 39.6°E), Antarctica in March 1997. The antenna pillar pin of the PRARE tracking antenna was tied to the International GPS Service for Geodynamics (IGS) antenna reference point by relative GPS positioning, and its International Terrestrial Reference Frame 1994 (ITRF94) coordinates were estimated as X_P=1766500.399m, Y_P=1460251.211m, and Z_P=-5932214.446m at the epoch of 1997.0. The total number of normal point data for range measurements attained almost 100% (around 2500min per week) from March to September, 1997; however, the number of received data decreased significantly thereafter. This may be due to a degraded X-band RF-cable under the cold temperature condition in the radome. Although an on-site tropospheric correction could not be made, post-processing with the surface synoptic data showed improvements of the overall root mean square (rms) range errors from about 50cm to 30cm. Application of the PRARE obtained precise orbits to radar altimeter and synthetic aperture radar studies will be discussed in a separate report. departmental bulletin paper